Synthesis and Structural Studies of Complexes of 4'-Methyl Acetophenone o-hydroxy 4-Benzamido Thiosemicarbazone with Oxovanadium(IV), Cobalt(II), Nickel(II) and Copper(II) - Arora, Rakhi; Singh, Neelam; Chaudhry, Shakshi; Vashisht, S.L. (Asian Journal of Chemistry, 2016)
Complexes of VO(IV), Co(II), Ni(II) and Cu(II) with 4'-methyl acetophenone o-hydroxy-4-benzamido thiosemicarbazone have been isolated and characterised on the basis of analytical data, molar conductance, magnetic susceptibility, electronic and infrared spectral measurements. Vanadyl complexes indicate square pyramidal geometry, while MLCI2(H2O)2, ML(CH3COO)2 [M=Co(II), Ni(II)], octahedral; and [Cu(L)CI2H2O)2, polymeric octahedral bridging and [Cu(CH3COO)2L)2, square pyramidal geometry around the metal ion, where L = (C17H18N4O2S).